Phytochemical characterization of phloem in maritime pine and stone pine in three sites in Portugal - Rita Simões; Carla Pimentel; Suzana Ferreira-Dias; Isabel Miranda; Helena Pereira (Heliyon, 2021)
This study analyzes the content and chemical profile of extractives present in the young phloem of mature trees of maritime pine (Pinus pinaster) and stone pine (P. pinea) in three sites in Portugal located in different climatic environments.The cross-sites average of extractives was similar in both pines with 38.5% in P. pinea and 37.7% in P. pinaster phloem. The hydrophilic fraction represented 82% and 70% of P. pinea and P. pinaster total extractives respectively, with large contents of phenolic compounds, flavonoids and tannins, and showed very high oxygen scavenging and reducing ability. Lipophilic extractives were present in higher proportion in P. pinaster phloem than in P. pinea phloem, and showed a large content of resin acids, with the predominance of abietic acid in P. pinaster, and dehydroabietic acid in P. pinea phloems, and of alkanoic acids.P. pinaster and P. pinea have specific defences related to phloem production of resin and phenolic compounds with the ratio phenolic-to-oleoresin compounds higher for P. pinea (4.7 vs 2.3 for P. pinaster) and constant in the three sites. The phytochemical content and composition of the young phloem of P. pinaster and P. pinea showed site differences highlighting the relationship between environment and metabolic production.